Validity and Reliability of a Revised Northampton Neonatal Skin Assessment Tool in Turkish Language - KARAKOÇ, AYŞE; KARACA, SEMRA (KOWSAR PUBL, 2017)
Background: It is important to check the skin of neonates on a daily basis so that abnormal conditions and skin problems are identified. Objectives: This study aimed at testing the validity and reliability of a revised Northampton Neonatal skin assessment tool in Turkish; a review to determine whether it is valid and reliable in the care of neonates. Methods: The research had a cross-sectional and methodological design. The data for the study was collected between 1st of January 2015, and 20th of June 2015, at the neonatal intensive care unit (NICU) of a major training and research hospital in Istanbul/Turkey; 362 neonatal skin assessments were executed. The revised tool's language, face, content, construct validity, and reliability were evaluated. Results: The intra-class correlation coefficient, which indicates interrater reliability, was 1.00 in the study, representing 100% agreement. The Cronbach alpha internal consistency coefficient revealed that the tool's general reliability was at an acceptable level (C alpha = 0.71). Although the model was not found to be significant (Chi-square = 46.22, df = 17, and P < 0.001), the other model fit indices found RMSEA < 0.07, chi(2)/df < 3, and SRMR< 0.06, which meant that the data had an acceptable fit for the model. The model exhibited a good fit because the CFI, NFI, GFI, and AGFI indices were close to 1. When the model fit indices were evaluated in combination, the CFA model generally had a good fit. The most significant and most prominent effect on the tool was the impact of NNS9 (level of care) indicator (b(9) = 0.86, t value = 17.46 > 1.96). Conclusions: The Turkish version of the revised northampton neonatal skin assessment tool is an appropriate, valid, and reliable instrument to be used in the assessment of neonatal skin, especially of infants at the NICU. The tool may be recommended for use in the care of neonates.
Keywords: Validity; Reliability; Neonatal; Skin Tool